Original article Registry of delays to primary percutaneous coronary intervention in patients with acute myocardial infarction in the province of Mazowsze in Poland – background, aims and methodology (PolAmi-Delay) - Maciejewski, Paweł; Witkowski, Adam; Karcz, Maciej; Szwed, Hanna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2007)
Background: In the province of Mazowsze, as in the rest of the Poland, patients with ST-segment-elevation myocardial infarction (STEMI) referred for primary percutaneous coronary intervention (pPCI) are an ever-growing group. Six high-volume PCI hospitals in Warsaw and three outside the capital offer modern invasive treatment. Current ESC guidelines for STEMI recommend pPCI as class IA indication as the preferred method of reperfusion in patients with typical chest pain lasting <12 h, provided pPCI can be performed by an experienced team within 90 minutes of the first medical contact. Nevertheless, a recent Swedish RIKS-HIA [1] registry indicates superiority of mechanical reperfusion over both in-hospital and pre-hospital fibrinolytic therapy, even if delay to pPCI exceeds this time. On the one hand, unlike the US or Western Europe, most Polish patients undergo inter-hospital transfer before they reach the cathlab, which prolongs the time to reperfusion treatment. On the other hand, in-hospital delay is relatively short in Poland. There are no comprehensive data yet as to total delay to pPCI in everyday clinical practice in Poland. Objective: The aim of the registry which commenced on the 1st of January 2007 is to evaluate treatment delays in consecutive patients with STEMI treated by pPCI in the province of Mazovia. Individual segments of the total delay will be analysed, as will be the demographics of patients, pharmacotherapy in the pre-hospital phase, and the influence of all these variables on short-term (30-day) and long-term (1-year) mortality. Adherence of routine management of MI patients to ESC guidelines will be evaluated. Methods: Delay intervals and clinical data of 2100 consecutive STEMI patients treated with pPCI in 9 interventional cardiology centres in Mazowsze will be registered. Data will be collected electronically using the database of the Working Group on Interventional Cardiology of the Polish Cardiac Society.